Avaliação auditiva comportamental em crianças com a síndrome da infecção congênita pelo Zika vírus - Santos, Walkiria Barbosa (2023)
The Zika virus belongs to the Flaviridae family and the Flavivirus type and it is related from an evolutionary point of view with other arboviruses transmitted by mosquitoes. Children with microcephaly associated with congenital Zika virus infection, based on the Health Ministry protocol may have delayed neuropsychomotor development with relevant motor and cognitive impairment, and sensory functions such as hearing may also be compromised, in some cases. It is likely that similar lesions are responsible for the auditory deficit in children with this infection. However, a concomitant central origin cannot be excluded and auditory behavioral evaluation may provide additional information. Objective: This study aims to evaluate the auditory behavior and the auditory function of children exposed to congenital Zika virus infection. Methods: This is a descriptive study. The collection was carried out in the speech therapy service of an audiology ambulatory of the Júlio Müller University Hospital, in the city of Cuiabá - Mato Grosso. Children aged between 5 and 7 years who were vertically infected with the Zika virus were included in this study. Results: Among the 11 children evaluated in the case group, 8 (72.7%) were female and 3 (27.3%) male, aged 5 to 7 years. Conclusion: In fact, in the population studied, a higher occurrence of changes in auditory development was found for children in the case group, associated with microcephaly, compared to the responses found in the control group population, suggesting that the Zika virus is really a risk factor for developing auditory abilites and auditory processing.